s/4 = 4

s =

Solve for s. pleae explain

5 answers

To solve the equation \( \frac{s}{4} = 4 \), we can follow these steps:

  1. Multiply both sides by 4: To eliminate the fraction, multiply both sides of the equation by 4. This will give us:

    \[ 4 \cdot \frac{s}{4} = 4 \cdot 4 \]

  2. Simplify both sides: The left side simplifies as follows:

    \[ 4 \cdot \frac{s}{4} = s \]

    And the right side becomes:

    \[ 4 \cdot 4 = 16 \]

    So now the equation is:

    \[ s = 16 \]

Thus, the solution is:

\[ s = 16 \]

In summary, we solved for \( s \) by multiplying both sides by 4 to eliminate the fraction, and then we simplified to find that \( s \) equals 16.

wait how'd you do the left side?

Let's break down the left side of the equation \( \frac{s}{4} = 4 \) more clearly.

  1. Initial Equation: Start with the equation: \[ \frac{s}{4} = 4 \]

  2. Multiply Both Sides by 4: To eliminate the fraction on the left side, we can multiply both sides of the equation by 4: \[ 4 \cdot \frac{s}{4} = 4 \cdot 4 \]

  3. Simplifying the Left Side: When you multiply \( 4 \) by \( \frac{s}{4} \), the 4s cancel each other out:

    • The 4 in the numerator (4 times \( s \)) remains, and the 4 in the denominator cancels out: \[ 4 \cdot \frac{s}{4} = \frac{4s}{4} = s \]

So you are left with: \[ s = 16 \]

  1. Right Side Calculation: For the right side:
    • Multiply out: \( 4 \cdot 4 = 16 \).

So after performing these calculations, we find that \( s = 16 \).

This step-by-step approach shows clearly how the left side simplifies to \( s \) after the multiplication. If you have any further questions or need more clarification, feel free to ask!

i still dont get it ahhh

No problem! Let's take it slow and really break it down. We're working with the equation:

\[ \frac{s}{4} = 4 \]

Step-by-Step Explanation:

  1. Understanding the left side: The expression \( \frac{s}{4} \) means "s divided by 4." So, if we wanted to eliminate the division by 4, we need to do the opposite operation, which is multiplying by 4.

  2. Multiply both sides by 4: To eliminate the fraction, we multiply both sides of the equation by 4. This looks like this:

    \[ 4 \cdot \left(\frac{s}{4}\right) = 4 \cdot 4 \]

  3. Focusing on the left side: Now, look closely at the left side \( 4 \cdot \frac{s}{4} \):

    • When you multiply \( 4 \) by \( \frac{s}{4} \), you can think of it as: \[ 4 \cdot \frac{s}{4} = \frac{4s}{4} \]
    • Here, the \( 4 \) in the numerator cancels with the \( 4 \) in the denominator, leaving us with just \( s \): \[ \frac{4s}{4} = s \]
  4. Calculating the right side: Now, for the right side: \[ 4 \cdot 4 = 16 \]

  5. Putting it together: Now our equation looks like this: \[ s = 16 \]

Conclusion:

So the solution is simply: \[ s = 16 \]

Why This Works:

  • The reason we multiply by 4 is to eliminate the division by 4. The operation of multiplying by 4 on both sides keeps the equation balanced, meaning the equality still holds.

If anything is still unclear, please let me know, and I can clarify further!